2006
DOI: 10.1074/jbc.m506804200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Endoplasmic Reticulum Stress in Hereditary Tyrosinemia Type I

Abstract: Hereditary tyrosinemia type I (HTI) is the most severe disease of the tyrosine degradation pathway. HTI is caused by a deficiency of fumarylacetoacetate hydrolase (FAH), the enzyme responsible for the hydrolysis of fumarylacetoacetate (FAA). As a result, there is an accumulation of metabolites such as maleylacetoacetate, succinylacetone, and FAA. The latter was shown to display mutagenic, cytostatic, and apoptogenic activities and to cause chromosomal instability. Herein, we demonstrate that FAA also causes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 49 publications
(50 reference statements)
2
24
0
1
Order By: Relevance
“…Studies on human HT1 and its animal models have shown that the accumulation of MAA, FAA, succinylacetoacetate, and succinylacetone causes direct tissue damage (Lindblad et al, 1977;Grompe et al, 1993;Sun et al, 2000;Aponte et al, 2001;Jorquera and Tanguay, 2001;Bergeron et al, 2006). In this study, we found that treatment of Arabidopsis wild-type seedlings with succinylacetone is able to mimic the sscd1 cell death phenotype (Fig.…”
Section: Discussionsupporting
confidence: 48%
“…Studies on human HT1 and its animal models have shown that the accumulation of MAA, FAA, succinylacetoacetate, and succinylacetone causes direct tissue damage (Lindblad et al, 1977;Grompe et al, 1993;Sun et al, 2000;Aponte et al, 2001;Jorquera and Tanguay, 2001;Bergeron et al, 2006). In this study, we found that treatment of Arabidopsis wild-type seedlings with succinylacetone is able to mimic the sscd1 cell death phenotype (Fig.…”
Section: Discussionsupporting
confidence: 48%
“…For example, treatment of cells in culture with purified FAA is able to cause a number of toxic effects including DNA mutagenesis, ER stress, oxidative stress, mitochondrial dysfunction, and activation of apoptosis (15)(16)(17)(18)20). Additionally, animals mutant for both HPD and FAH that are given homogentisate demonstrate the rapid development of liver and kidney damage (14,50).…”
Section: Conservation Of the Tyrosine Degradation Pathway In Worms-mentioning
confidence: 99%
“…Organ damage is likely due to the accumulation of MAA, FAA, and their conversion to succinylacetoacetate (SAA) and succinylacetone (SA) (12). These compounds are highly reactive electrophiles, which can damage proteins and DNA leading to the activation of several stress response pathways as well as apoptotic pathways (13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Clinical study revealed that targeted therapy against TNF-α could downregulate epithelial cell apoptosis and promotes barrier repair in active Crohn's disease [26]. Mutant mouse with TNF-α overexpression may cause IEC FFA (fumarylacetoacetate) accumulation [27], which has been proven as a potent inducer of ER stress [28]. Since whether TNF-α alone could induce ER stress and apoptosis is controversial in vitro [29], and previous studies revealed that IFN-γ prime the response of Caco-2 cells to TNF-α through induction of TNFR2 expression [15] or potentiating TNF-related apoptosis-inducing ligand [30], a combination of IFN-γ and TNF-α was used.…”
Section: Discussionmentioning
confidence: 99%